2006
DOI: 10.1377/hlthaff.26.1.w68
|View full text |Cite
|
Sign up to set email alerts
|

Taking Steps Toward Integration

Abstract: If patients are to be at the center of health care, then providers should work diligently to better organize the delivery system. In this Perspective, two Mayo Clinic leaders provide their views on why it is necessary for physicians and hospitals to set aside their differences and work together for the good of their patients. They cite successful enterprises nationwide that combine hospital and physician control. T h e s e v e n t e e n t h -c e n t u ry poet John Donne points out a simple truth that can guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Considering the confluence of these forces, it is not surprising that Hospital-Physician Relationships (HPRs) are an important area of academic research and a key concern of hospital managers and health policy makers. Moreover, given the central important role of physicians in hospital care delivery, it has been shown that HPRs have an impact on quality of provided care [ 8 ], hospitals’ financial performance [ 9 ] and cost-effectiveness of health care delivery [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the confluence of these forces, it is not surprising that Hospital-Physician Relationships (HPRs) are an important area of academic research and a key concern of hospital managers and health policy makers. Moreover, given the central important role of physicians in hospital care delivery, it has been shown that HPRs have an impact on quality of provided care [ 8 ], hospitals’ financial performance [ 9 ] and cost-effectiveness of health care delivery [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical integration will require more than meaningful use of health information technology (HIT) and information exchange (Robert Wood Johnson Foundation, 2012; Tello-Leal et al 2012). To improve the delivery system, health informatics integration is needed (Wan, 2006; Cortese and Smoldt, 2007). Furthermore, the current view on integration in ACOs is that the integration is not only a structural change, but also a cultural change (Kreindler et al 2012).…”
Section: Related Researchmentioning
confidence: 99%
“…Halvorson (2009) places the emphasis on shared information as an instrument for the coordination of providers. Cortese and Smoldt (2007) add to this more coordinated hospital-physician relationships within various forms of integrated delivery systems (physician or hospital-led), as well as new business environments and payment policies.…”
Section: Conceptual Framework For Integration Evaluationmentioning
confidence: 99%